Postać celebrytki w operze: rozwiązła księżna i króliczek „Playboya” - Bogucki, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The aim of the article is to analyse two British contemporary operas: Thomas Adès’s Powder Her Face and Mark Anthony Turnage’s Anna Nicole from the perspective of celebrity studies. Both of these works were inspired by the biographies of celebrities – Margaret Campbell, Duchess of Argyll’s and Anna Nicole Smith’s. The text analyses how their biographies were edited both in literary and musical terms, attempting to determine to what extent they are either pioneering or embedded in the traditions of the opera.